Zakat Recipients' Satisfaction on Housing Programme - Mohit, Mohammad Abdul; Nazyddah, Nurul (IIUM Press, 2015)
n Malaysia, low-cost housing is usually provided through both the public and private sectors. Public sector provisions are mostly concentrated in large urban centres such as Kuala Lumpur, George Town, and in the rural areas as well, while private sector operates in both urban and suburban areas. Recently, the Selangor Zakat Board (SZB) has started to participate in the provision of low-cost housing in the state of Selangor, Malaysia, and up to 2007, 906 units, which accounts for a little over 1% of total low-cost housing in the state, have been delivered under its different programmes. Although low-cost housing delivered by the public and private sectors have been widely studied in Malaysia, so far no study has been undertaken to examine the effectiveness of the zakat-funded housing programmes in the country. This paper, therefore, intends to evaluate the important SZB housing programmes by adopting the housing satisfaction approach which is currently used as a customer satisfaction tool for evaluating public/ private housing in many local governments in UK and USA.